Між почуттям та інтелектом: філософія любові в романі Євгена Плужника «Недуга» - Гірняк, М. (Слово і Час, 2022)
У статті зосереджено увагу на основних вимірах любові, представлених в
інтелектуальному романі Є. Плужника «Недуга», окреслено соціокультурне підґрунтя порушеної у творі проблематики та висвітлено взаємозв’язок
рефлексій про любов зі спробами осягнути особливості буття людини у сві-
ті. Методологічну базу дослідження сформували праці з філософської та літературної антропології, психоаналізу та герменевтики. Незважаючи на
ідеологічний контекст епохи, яка ставила під сумнів можливість кохання
між представниками ворожих суспільних класів і право «нової» людини на
любов, персонажі роману розмежовують любов-пристрасть, любов-дружбу,
сімейну любов та справжню любов, готову визнавати Іншого в його інакшості. Вони також прагнуть збагнути науку життя, замислюються над
власною ідентичністю та маркерами людської сутності. The primary aim of the paper is to clarify the main approaches to the philosophy of love, represented
in the intellectual novel “The Desease” by Yevhen Pluzhnyk, to outline the sociocultural
footing of the issues, raised in the work, as well as to bring to light the relationship of
reflections on multidimensionality of love and the characters’ attempts to comprehend the
peculiarities of human existence in the world. The methodological premises and theoretical
frameworks for the research were provided by the studies on psychoanalysis, hermeneutics,
philosophical and literary anthropology. While trying to understand the essence of love,
the characters of Pluzhnyk’s novel, like the philosophers from different epochs, distinguish
among love-passion, love-friendship, family love, which is developed in the matrimony, and
‘true love’ that is close to the divine one. The ‘true love’ is a willingness to sacrifice as well as
realizing the uniqueness of other person; it motivates to feel responsibility for Other and to
see him/her not from a selfish but from a values-based perspective.
However, the relationships between the characters along with their reflections on love
in the novel by Pluzhnyk are not an ordinary illustration of the different philosophical concepts.
The writer also actualizes the ideological context of the 1920s and encourages his
characters to think whether love between the representatives of the hostile social ‘classes’
is possible and whether the ‘new’ human has the right to love at all. Comprehension of
the phenomenon of love in the novel “The Desease” is intertwined with the reflections on
the identity of the person, on his/her internal crisis, provoked by the rationalistic approach
to life, as well as on the peculiarities of the dialogue with the Other. The characters of the
novel also seek to understand ‘the science of life’, to solve the problem of separating private
and public spaces of existence, to grasp the contradistinction of the value positions ‘to take’,
aimed at the self, and ‘to give’, which is laid in the basis of love and appears to be an important
feature of the human entity.